DEEP BELIEF NETWORK BASED DISEASE DETECTION IN PEPPER LEAF FOR FARMING SECTOR. - JANA, S.; BEGUM, A. RIJUVANA; SELVAGANESAN, S.; SURESH, P. (Turkish Journal of Physiotherapy Rehabilitation, 2021)
More than a decade, the leaf was affected with various disease in farming of various crops which directly degrades the crop yield in agriculture leads to huge loss. It is necessary to detect various disease which affect the leaf and to take precautionary actions to increase the crop yield. In this paper an automated system is proposed with imaging techniques (acquisition, feature extraction, classification). The real time image is analyzed with Deep Belief Network classifier to automate the various disease from the training data sets with the predefined data sets. The results reported in this article give better performance over the existing methods which directly having relation to increase the crop yields.